Региональные тенденции экстремумов стока рек Беларуси - Данилович, И. С.; Тарасевич, И. В.; Квач, Е. Г.; Гледко, Ю. А. (Минск : БГУ, 2024)
В работе представлен анализ изменения режима рек в различные фазы гидрологического цикла для трех речных водосборов (р. Западная Двина, р. Неман и р. Днепр). Показаны региональные тенденции изменения экстремальных гидрологических характеристик рек Беларуси в различные фазы водного цикла, связанные с таянием снегов, сильными дождями и засухами The paper presents an analysis of changes in river regime during various phases of the hydrological cycle for three river catchments (the Western Dvina River, the Neman River and the Dnieper River). The major results concern regional trends in extreme hydrological characteristics of Belarusian rivers in various phases of the water cycle associated with snow melting, heavy rains and droughts